Risks and predictive biomarkers of SUDEP - Ryvlin, Philippe (Curr Opin Neurol, 2019)
- PURPOSE OF REVIEW: This review updates our knowledge regarding SUDEP risks, risk factors, and investigations of putative biomarkers based on suspected mechanisms of SUDEP. - RECENT FINDINGS: The overall incidence of SUDEP in adults with epilepsy is 1.2/1000 patient-years, with surprisingly comparable figures in children in recently published population-based studies. This risk was found to decrease over time in several cohorts at a rate of −7% per year, for unknown reasons. Well-established risk factors include frequency of generalized tonic-clonic seizures, while adding antiepileptic treatment, nocturnal supervision and use of nocturnal listening device appear to be protective. In contrast, recent data failed to demonstrate the predictive value of heart rate variability, periictal cardiorespiratory dysfunction, and postictal generalized EEG suppression. Preliminary findings suggest that brainstem and thalamic atrophy may be associated with a higher risk of SUDEP. Novel experimental and human data support the primary role of GTCS-triggered respiratory dysfunction and the likely contribution of altered brainstem serotoninergic neurotransmission, in SUDEP pathophysiology. - SUMMARY: While significant progress has been made during the past year in the understanding of SUDEP mechanisms and investigation of numerous potential biomarkers, we are still missing reliable predictors of SUDEP beyond the well-established clinical risk factors.